Force Structure and Local Peacekeeping Effectiveness: Micro-Level Evidence on UN Troop Composition. - Dworschak, Christoph; Cil, Deniz (International Studies Quarterly, 2022)
In recent years, researchers have shifted their focus to studying the effects of peacekeeping in a geographically disaggregated manner. One of the factors that is yet to be fully examined is the variation among peacekeeping troops at the local level and its impact on peacekeeping effectiveness. Specifically, peacekeeping troops greatly vary across two dimensions: unit types, e.g. infantry, engineering, aviation, etc. and their country of origin. We argue that mixing different unit types increases peacekeepers' specialization in skills and equipment, thereby improving their effectiveness. However, this effect is moderated by the diversity of troop contributing countries (TCCs), which exacerbates coordination problems among troops. We explore our mechanisms using evidence from interviews with former and active peacekeepers and test the empirical implications using new subnational data on UN peacekeeping bases. Our results show that diverse unit types from culturally similar TCCs are better at deterring battle-related violence, yet the same conditional effect is not present for deterring one-sided violence. These findings are of major relevance to the ongoing academic debate on peacekeeping composition, as well as to practitioners in international organizations.